Reliability analysis of offshore structures under earthquake excitation - Tan, Qing Hong. (2009)
Our world today depends heavily on oil and gas for energy needs. Without them, our society would grind to a standstill. We would not be able to produce electricity and there would be no cars travelling on the roads.